2008
DOI: 10.1017/s002531540800060x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the blackmouth catshark, Galeus melastomus (Chondrichthyes: Scyliorhinidae) off the Languedocian coast (southern France, northern Mediterranean)

Abstract: The blackmouth catshark, Galeus melastomus presents a wide Atlanto-Mediterranean distribution, and is commonly captured off the Languedocian coast (southern France, northern Mediterranean). The males and females sexually matured between 510–550 mm and 520–610 mm total length (TL), respectively. The largest male and the largest female were 620 mm and 640 mm TL, respectively. There was a significant relationship of total liver mass vs TL between males and females. The diameter of the largest yolky oocytes ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 17 publications
11
45
0
10
Order By: Relevance
“…The highest value of HSI was recorded in juvenile male and female specimens suggested that liver constituted a reserve of nutriments for free-swimming specimens soon after parturition, this hypothesis was corroborated by decreasing of HSI values in larger juveniles. Both HSI and GSI values were lower in G. altavela, similar to those recorded by Capapé et al (2007) for the eagle ray, Myliobatis aquila (Linnaeus, 1758), a matrotrophic species (sensu Hamlett et al 2005) in which the mother supplements yolk from other sources such as uterine secretions, the phenomenon was called histotrophy by Hamlett et al (2005). Additionally, the high CBD value, 22.5, of G. altavela from the Syrian coast is lower than this calculated for the Tunisian specimens which reached 30.6; such difference is due to the fact that mass of fully yolky oocytes were used for calculate CBD of latter specimens, while in the presently reported study we have used the mass of fertilized eggs, which was slightly higher because they were surrounded during ovulation by a jellylike structure which did not exist in fully yolky oocytes.…”
Section: Body Of Watersupporting
confidence: 75%
“…The highest value of HSI was recorded in juvenile male and female specimens suggested that liver constituted a reserve of nutriments for free-swimming specimens soon after parturition, this hypothesis was corroborated by decreasing of HSI values in larger juveniles. Both HSI and GSI values were lower in G. altavela, similar to those recorded by Capapé et al (2007) for the eagle ray, Myliobatis aquila (Linnaeus, 1758), a matrotrophic species (sensu Hamlett et al 2005) in which the mother supplements yolk from other sources such as uterine secretions, the phenomenon was called histotrophy by Hamlett et al (2005). Additionally, the high CBD value, 22.5, of G. altavela from the Syrian coast is lower than this calculated for the Tunisian specimens which reached 30.6; such difference is due to the fact that mass of fully yolky oocytes were used for calculate CBD of latter specimens, while in the presently reported study we have used the mass of fertilized eggs, which was slightly higher because they were surrounded during ovulation by a jellylike structure which did not exist in fully yolky oocytes.…”
Section: Body Of Watersupporting
confidence: 75%
“…reproductiove symetry observed in the common eagle ray Myliobatis aquila (Capapé et al 2007)], is very widespread in Myliobatiformes. Most species show reproductive asymmetry related to development and functionality of ovaries and uteri (Hamlett et al 1985;Smith & Merriner 1986;Johnson & Snelson 1996;White et al 2001;Neer & Thompson 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Caution should be taken with these results, because G. melastomus shows no significant trend for the same period. This species should have a higher resilience than E. spinax because of its shorter reproductive cycle and higher fecundity (Capapé et al, 2008). Furthermore, there is no comparable time series of the abundance of E. spinax in Algerian waters, so its trend during the same period is unknown.…”
Section: Discussionmentioning
confidence: 99%